Molecular Mechanisms Of Mitragynine Inhibition On Herg1a/1b Channel - Tay, Yea Lu (2018)
The leaves of Mitragyna speciosa Korth (M. speciosa), commonly known as ketum in Malaysia, have been widely used to treat common illnesses such as intestinal infections, muscle pain, cough, diarrhea, diabetes, hypertension and to improve blood circulation. Nevertheless, there are growing concerns about the safety and abuse or misuse potentials of the plant which exhibits addictive effects. The safety profile of the plant is not fully elucidated. The human ether-a-go-go-related gene 1 (hERG1) encodes the pore-forming subunit underlying cardiac rapidly delayed rectifier potassium current (IKr).